PENINGKATAN KUALITAS SERVICE KEBERSIHAN DENGAN METODE CUSTOMER SATISFACTION INDEX (CSI) DI INSTALASI GIZI RSUP FATMAWATI RAYA. - Bastuti, Sofian (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2023)
Patient satisfaction will be achieved if hygiene services at the nutrition installation are provided according to their needs, Fatamawati Raya Hospital is a research place to determine the level of satisfaction of cleaning servicessin the nutrition installation. Based on research conducted at Fatmawati Raya Hospital, with the technique of distributing questionnaires to patients so as to collect 381 respondents using the CSI (Customer Satisfaction Index) method, it can be concluded that the level of patient satisfaction with the cleaning services of nutritional installations needs to be maintained, because it is in accordance with patient expectations where the cleaning services of nutritional installations are very good. The purpose of this study is to determine and maintain the quality of hygiene services in nutrition installations so that they can continue to satisfy patients. To determine the level of patient satisfaction, researchers analyzed five dimensions of quality, namely tangibles, reliability, responsiveness, assurance and empathy. The method is a consumer satisfaction index by determining the Mean Importance Score (MIS) of each variable, making Weight Factors (WF) per variable. This weight is the percentage of MIS value per variable to the total MIS of all variables, Determines the Mean Satisfaction Score (MSS) of each attribute, Makes a Weight Score (WS) of each variable. This weight is the percentage of MIS value per variable to the total MIS of all variables, Determines the Mean Satisfaction Score (MSS) of each attribute, Makes a Weight Score (WS) of each variable. This weight is a multiplication between WF and MSS, so the results of the level of customer satisfaction of Fatamawati Raya Hospital will be obtained. From the results of the analysis, it shows that the level of patient satisfaction with the cleaning services of nutrition installations based on CSI is 61.68%.